2008
DOI: 10.4103/1596-3519.55686
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy: Indications at university of Calabar teaching hospital, Calabar, Nigeria

Abstract: Background/objective: The relative rarity of gallbladder disease has been documented in various parts of Africa. Recently the incidence has been reported as rising in some African countries. We undertook this study to evaluate the indications for cholecystectomy in our center and compare with others. Methods: This is a retrospective study of 18 open cholecystectomies in 10years. Results: The ages ranged from 13 and 65 years (mean 39.2years). There were 15 females and 3 males (F: M = ratio 5:1). Calculous chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
15
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 3 publications
14
15
1
Order By: Relevance
“…So the classification of various histomorphological types of gallbladder lesions is important to categorize into non-neoplastic and neoplastic lesions of gallbladder. (13) In the present study gallbladder lesions were more common in females than in males with a male to female ratio of 27:79 which was similar to other studies carried out by N. T. Damor a, et (14) , Tadashi Terada et al (15) , Dr. Gudeli Vahini, et.al (16 ) , Asuquo et al (17) , Tantia et al (18) reported male to female ratio 1:2.3, 213:327 , 1:1.5, 1:5, 1:2.8 respectively. N. T. Damor et al (14) and Khanna et al (19) reported that majority of non-neoplastic lesions of Gallbladder occurred in 3rd to 5th decades.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…So the classification of various histomorphological types of gallbladder lesions is important to categorize into non-neoplastic and neoplastic lesions of gallbladder. (13) In the present study gallbladder lesions were more common in females than in males with a male to female ratio of 27:79 which was similar to other studies carried out by N. T. Damor a, et (14) , Tadashi Terada et al (15) , Dr. Gudeli Vahini, et.al (16 ) , Asuquo et al (17) , Tantia et al (18) reported male to female ratio 1:2.3, 213:327 , 1:1.5, 1:5, 1:2.8 respectively. N. T. Damor et al (14) and Khanna et al (19) reported that majority of non-neoplastic lesions of Gallbladder occurred in 3rd to 5th decades.…”
Section: Discussionsupporting
confidence: 81%
“…The present study is comparable to the above studies with the ratio of non-neoplastic to neoplastic lesion was 20:1. Asuquo et al (17) reported that out of 18 specimens studied 9(50%) specimens shows calculous cholecystitis, 8(44.4%) have acalculous cholecystitis and 1(5.6%) has carcinoma of gallbladder. Shrestha et al (22) In the our study, among all the lesions of gallbladder, 66 cases (62.2%) were diagnosed as chronic cholecystitis with cholelithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…In present study, lesions of gall bladder were more common in females than in males with a male to female ratio of 1:3.91 which was similar to other study carried out by Rahul et al [4], Asuquo et al [5], Tantia et al [6] and John et al [7], reported male to female ratio of 1:4.8; 1:5, 1:2.8 and 1:4 respectively. Most of the patients presented with pain upper abdomen, nausea and/or vomiting, which is consistent with findings by Laghari et al [8].…”
Section: Discussionsupporting
confidence: 80%
“…[3][4] The condition is rare among indigenous Africans including Nigerians. [5][6][7] However, a recent epidemiologic review of gallstone incidence in Nigeria suggests an increasing trend of the condition owing to the westernization of dietary habits among Nigerians. [6][7][8] The mechanism of gallstone formation is vague in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] However, a recent epidemiologic review of gallstone incidence in Nigeria suggests an increasing trend of the condition owing to the westernization of dietary habits among Nigerians. [6][7][8] The mechanism of gallstone formation is vague in the literature. 9,10 The proposed theories of its etiopathogenesis include supersaturation of bile and resultant precipitation of one or more of the primary biochemical constituent of bile (cholesterol, triglycerides, bilirubin, calcium salts, proteins, and other lipids and minerals), biliary infection, drugs, and impaired motility of the gallbladder secondary to spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%